Sport for Social Justice, Capability, and the Common Good A Position Statement in Honor of Tessa Jowell - Jarvie, Grant 1955-; Ahrens, Susan (2019)
There is a continuing debate about the contribution of sport and sport for development and peace (SDP) to both the theory and practice of social justice. At the same time the policy world is showing strong indications that it is seeking politically smarter ways of understanding what it means to foster social justice, development, and inclusive peace processes. This position statement is committed to sport actively being seen to be playing a part in addressing the challenges that face humanity in the 21st century. The proposition is that sport and SDP are served well by a capability approach (CA) as a framework that enables the construction of the common good. The article considers a CA for social justice prior to a discussion of sport, capability, and the common good, which positions sport as a resource of hope in fostering politically smarter cultural relations.
Keywords: Capability; Common Good; influence; social justice; Sport